2003
DOI: 10.1101/gad.1109003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical analyses of DNA and RNA binding by a bifunctional homing endonuclease and group I intron splicing factor

Abstract: We determined the crystal structure of a bifunctional group I intron splicing factor and homing endonuclease, termed the I-AniI maturase, in complex with its DNA target at 2.6 Å resolution. The structure demonstrates the remarkable structural conservation of the ␤-sheet DNA-binding motif between highly divergent enzyme subfamilies. DNA recognition by I-AniI was further studied using nucleoside deletion and DMS modification interference analyses. Correlation of these results with the crystal structure provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 55 publications
4
87
1
1
Order By: Relevance
“…S2A). Both proteins make contacts with approximately one-half of the nucleotide bases and backbone phosphate groups of their target sequences, via a mixture of direct and water-mediated contacts, as observed in previous LHE crystal structures (16)(17)(18) (Fig. 2B).…”
Section: Global Analyses Of Single-chain Laglidadg Enzymes Reveals DIsupporting
confidence: 66%
“…S2A). Both proteins make contacts with approximately one-half of the nucleotide bases and backbone phosphate groups of their target sequences, via a mixture of direct and water-mediated contacts, as observed in previous LHE crystal structures (16)(17)(18) (Fig. 2B).…”
Section: Global Analyses Of Single-chain Laglidadg Enzymes Reveals DIsupporting
confidence: 66%
“…This analysis revealed a series of conserved basic residues distributed across the protein, at positions removed from the DNA binding site ( Fig. 1A; Bolduc et al 2003). A single glutamate substitution in one of the conserved residues (arginine 239 [R239E]) four residues from the C terminus resulted in a 10-fold decrease in A. nidulans COB pre-RNA splicing and ribonucleoprotein (RNP) dissociation rates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, half of known maturases also retain homing activity (Dalgaard et al 1997;Lambowitz et al 1999). Finally, comparison of the threedimensional structures between a dual function maturase/ endonuclease from Aspergillus nidulans (I-AniI) with a number of other homing endonucleases shows that both types of proteins share a conserved overall topology (Bolduc et al 2003). While the mechanisms by which homing endonucleases recognize and cleave their target sequences are well established, how such proteins bind with high specificity to their intron RNA substrates and promote RNA splicing is only beginning to be uncovered (Ho and Waring 1999;Solem et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The Ca 2ϩ atom is hexa-coordinated with phosphates from both DNA strands (2A strandA and Ϫ3C strandB ), 3 water molecules and D21 from the first LAGLI-DADG motif. The additional anomalous difference study in the presence of Mn 2ϩ demonstrated binding of 2 metal ions with equivalent occupancy, similarly to the Mg 2ϩ positions reported for I-AniI (20) (Fig. 2B and Fig.…”
Section: Resultsmentioning
confidence: 52%